Antivirulence activities of retinoic acids against Staphylococcus aureus - Park, Inji; Lee, Jin-Hyung; Ma, Jin Yeul; Tan, Yulong; Lee, Jintae (Frontiers in Microbiology, 2023)
Multidrug-resistant bacteria such as Staphylococcus aureus constitute a global health problem. Grampositive S. aureus secretes various toxins associated with its pathogenesis, and its biofilm formation plays an important role in antibiotic tolerance and virulence. Hence, we investigated if the metabolites of vitamin A1 might diminish S. aureus biofilm formation and toxin production. Of the three retinoic acids examined, 13-cis-retinoic acid at 10 μg/mL significantly decreased S. aureus biofilm formation without affecting its planktonic cell growth (MIC > 400 μg/mL) and also inhibited biofilm formation by Staphylococcus epidermidis (MIC > 400 μg/mL), but less affected biofilm formation by a uropathogenic Escherichia coli strain, a Vibrio strain, or a fungal Candida strain. Notably, 13-cisretinoic acid and all-trans-retinoic acid significantly inhibited the hemolytic activity and staphyloxanthin production by S. aureus. Furthermore, transcriptional analysis disclosed that 13-cisretinoic acid repressed the expressions of virulence-and biofilm-related genes, such as the twocomponent arlRS system, α-hemolysin hla, nuclease (nuc1 and nuc2), and psmα (phenol soluble modulins α) in S. aureus. In addition, plant and nematode toxicity assays showed that 13-cis-retinoic acid was only mildly toxic at concentrations many folds higher than its effective antibiofilm concentrations. These findings suggest that metabolites of vitamin A1, particularly 13-cis-retinoic acid, might be useful for suppressing biofilm formation and the virulence characteristics of S. aureus.